Incidence of acalculus cholecystitis in Dengue Fever - A Prospective Study - DR.M.K.NISHAANTH,; DR.N.N.ANAND, (International Journal of Pharma and Bio Sciences, 2018)
Dengue Fever (DF) is a tropical disease and one of the commonest arbo-viral diseases.It is caused by single stranded RNA – flavivirus. It is transmitted by the mosquito bite. The female Aedesaegypti mosquito is the vector. Dengue fever is a non-specific and self-limiting febrile illness. The presentation may range from asymptomatic illness to dengue fever, dengue hemorrhagic fever and dengue shock syndrome. Sometimes it presents with unusual presentations such as acute acalculuscholecystitis. It may be interpreted as a surgical emergency. In acute acalculuscholecystitis, patient presents with features of right upper quadrant pain and murphy’s sign positive.The current study is a prospective study of the incidence of acalculuscholecystitis in dengue fever patients admitted in SreeBalaji Medical College And Hospital, chromepet, Tamilnadu. Total no of patients with confirmed dengue fever were 50. The diagnosis was according to the clinical manifestations and laboratory investigations. The diagnosis was confirmed by a positive IgM antibody test. The diagnosis of acute acalculouscholecystitis was made according to clinical features and sonographic findings. Among these, number of patients who developed the complication of acute acalculuscholecystitiswere 13. In this study, the incidence of acalculouscholecystitis in dengue fever patients observed was 26 %. The incidence is higher when compared to other similar studies, indicating the increasing incidence of acalculouscholecystitis in the present.Thus,knowledge of the condition is needed for timely recognition and management.